2014
DOI: 10.5455/2320-1770.ijrcog20140981
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum lipid profile in cases of pre-eclampsia and eclampsia

Abstract: Background: According to the current knowledge, rise in the serum triglyceride level is a major contributor in the pathogenesis of preeclampsia and eclampsia. The present study was designed to compare the changes in lipid profile in normal pregnancy, pre-eclampsia & eclampsia cases. Methods: A case control study was done consisting of total 100 study subjects, 75 already diagnosed pre-eclamptic & eclamptic women and 25 normotensive pregnant women. Age range was 18-35 years, gestational age 28 weeks to term wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
3
3
0
Order By: Relevance
“…The mean serum triglyceride level of the current study was significantly higher in preeclamptic women than normotensive pregnant women (228.04 ± 91.38 and 145.67 ± 121.61), respectively and its pooled SMD was (SMD = 1.61, 95% CI: 1.03, 2.14). Similar, findings were reported in the studies conducted in China and Pakistan [ 36 , 38 , 39 ]. In the prospective cohort study conducted in Netherlands, hypertriglyceridemia were associated with pre-eclampsia and high blood pressure in the early pregnancy [ 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…The mean serum triglyceride level of the current study was significantly higher in preeclamptic women than normotensive pregnant women (228.04 ± 91.38 and 145.67 ± 121.61), respectively and its pooled SMD was (SMD = 1.61, 95% CI: 1.03, 2.14). Similar, findings were reported in the studies conducted in China and Pakistan [ 36 , 38 , 39 ]. In the prospective cohort study conducted in Netherlands, hypertriglyceridemia were associated with pre-eclampsia and high blood pressure in the early pregnancy [ 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…Significant rise of serum triglyceride concentrations in our study has been corroborated in various other studies [20,[22][23][24][25] . A 4.15-fold increase in the risk of pre-eclampsia among women with triglyceride levels >133 mg/dL (95% CI 1.50 to 11.49) has been reported by Enquobahrie DA et al [20] .…”
Section: Discussionsupporting
confidence: 92%
“…Numbers of mechanisms have been proposed for the development of pre-eclampsia; though, endothelial dysfunction leading to the oxidative stress and contributing to the altered lipid profile in women with pre-eclampsia have been considered as a significant risk factor in previous studies 6 . It has been suggested that dyslipidemia in the beginning of pregnancy has high risks of pre-eclampsia and eclampsia 7 . Increased serum or plasma triglyceride (TG) concentration greater than 1.6 mmol/l is referred as hypertriglyceridemia.…”
Section: Introductionmentioning
confidence: 99%